2013
DOI: 10.1055/s-0033-1350978
|View full text |Cite
|
Sign up to set email alerts
|

Plants: A Source for New Antimycobacterial Drugs

Abstract: alkaloids l " flavonoids l " chalcones l " coumarins l " lignans l " phenols l " terpenes l " chromones l " alkane l " alkene l " plants l " Mycobacterium tuberculosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 71 publications
1
52
0
2
Order By: Relevance
“…The biological activity of the LSE may, perhaps, be due to the presence of fatty acid components, especially the oleic and palmitic fatty acids. Santhosh and Suriyarayanan [17], revealed that fatty acids such as oleic acid and linoleic acid exhibited activity against MDR forms of M. tuberculosis. In another study, Juan et al, [18] reported the anti-tubercular activity of linoleic, oleic and palmitic acids found in essential oils from Citrus species.…”
Section: Concentration Of Lse (%) Lsementioning
confidence: 99%
“…The biological activity of the LSE may, perhaps, be due to the presence of fatty acid components, especially the oleic and palmitic fatty acids. Santhosh and Suriyarayanan [17], revealed that fatty acids such as oleic acid and linoleic acid exhibited activity against MDR forms of M. tuberculosis. In another study, Juan et al, [18] reported the anti-tubercular activity of linoleic, oleic and palmitic acids found in essential oils from Citrus species.…”
Section: Concentration Of Lse (%) Lsementioning
confidence: 99%
“…Moreover [39], the majority of new drugs introduced in the United States are derived primarily from the plants. As discussed, most of the chemical drugs cause adverse effects and are costlier, therefore, nowadays there is an increasing inclinations towards the use of an alternative source of medicine, especially based on medicinal plants [40]. A number of medicinal plants have been reported for anti-mycobacterial activity across the globe [41]- [46].…”
Section: Medicinal Plants For Tuberculosismentioning
confidence: 99%
“…Different plant extracts containing a variety of terpenoids, such as monoterpenes, sesquiterpenes, diterpenes and triterpenes, have been reported to possess moderate to significant biological activity against M. tuberculosis [8,9]. Croton tonkinensis, belonging to the Euphorbiaceae family, is an herbal shrub that grows in tropical areas and is abundant in Vietnam.…”
Section: Introductionmentioning
confidence: 99%